Applying Effect the Reciprocal Teaching Model to Mathematics Anxiety - Melani Felantini Putri; Molli Wahyuni (International Journal of Educational Dynamics, 2021)
The background of this research is the lack of self-confidence of students when learning mathematics which is characterized by feelings of fear or worry that are owned by class VIII students of MTs Negeri 3 Kampar. One solution to overcome this problem is to use the reciprocal teaching learning model. The purpose of this study was to find out that the reciprocal teaching learning model could reduce the mathematical anxiety of Grade VIII students at MTsN 3 Kampar. This research is a quasi-experimental study using nonequivalent control group design. The research subjects consisted of 18 students from class IIC and 18 students from VIIID. The sample technique used is purposive sampling. The data collection technique used is the math anxiety questionnaire. The results of this study can be concluded that the reciprocal teaching learning model can reduce the math anxiety of class VIII students of MTs Negeri 3 Kampar. This can be proven through the left side test with a sig (2-tailed) value of 0.0185 <0.025.